The relationship between hamstring muscle morphology, physical activity, dynamic balance, and knee functions among post-operative anterior cruciate ligament reconstruction patients - Radika, I Komang Saskaraning; Adhitya, I Putu Gede Surya; Kinandana, Gede Parta (PT. Kesehatan Gerak Fungsi Tubuh, 2025)
Introduction: Anterior cruciate ligament (ACL) injuries are common in pivot sports, particularly soccer and volleyball, with soccer accounting for the majority. ACL reconstruction often leads to morphological changes, and lower extremity balance plays a key role in knee function recovery. This study aimed to examine the relationship between hamstring muscle morphology and physical activity (GLTEQ), dynamic balance (Y-Balance Test), and knee function (KOOS) in post-ACL reconstruction patients. Methods: This study employed a literature review method, sourcing articles from PubMed, Google Scholar, and the Journal of Sport Rehabilitation. Keywords included 'hamstring muscle morphology,' 'Godin Leisure-Time Exercise Questionnaire,' 'Y-Balance Test,' 'Knee Injury and Osteoarthritis Outcome Score,' and 'anterior cruciate ligament reconstruction.' Boolean operators 'AND' and 'OR' were used to refine the search. Results: Subjects with ACLR showed reduced muscle volume and lower Y-Balance Test scores compared to healthy controls. They also scored significantly lower across all KOOS subscales (p < 0.01). The KOOS Sport and Recreation subscale was marginally associated with GLTEQ scores (p = 0.057). Additionally, GLTEQ scores were lower in the ACLR group than the modified GLTEQ scores in healthy participants (p = 0.58). Conclusion: Hamstring muscle morphology was significantly associated with Y-Balance Test performance, while no significant relationship was found between KOOS or GLTEQ scores in post-ACL reconstruction patients.